Integrasi Konsep Sustainable Architecture dalam Pengembangan Kawasan Wisata Pantai Kurenai - Rizaldi Djaba; Beby Sintia Dewi Banteng; Ria Selfiyani Bahrun (Jurnal Ilmu Teknik Terapan, 2025)
The Kurenai Beach tourism area in Gorontalo has high natural potential, but suboptimal environmental and infrastructural conditions, such as garbage pollution and lack of facilities, can reduce its appeal to tourists. This research aims to develop the Kurenai Beach area by integrating the concept of Sustainable Architecture as an effective solution to increase tourist attraction while preserving the environment. The research method used is a case study with a descriptive qualitative approach. Data collection was carried out through observation, surveys, and documentation to obtain spatial data and analyze space needs, material selection, and waste management. The design integrates social, economic, and environmental aspects in a sustainable design. Its implementation includes the use of natural lighting and cross-ventilation, as well as the use of renewable energy through solar panels. The materials used are from local, eco-friendly sources such as bamboo, clay, and wood. Additionally, the socio-economic aspect is strengthened with facilities that empower local communities, such as food stalls serving fishermen's catches. To preserve the environment, the area is equipped with a waste bank and an efficient waste management system. This approach aims to make Kurenai Beach a model for sustainable tourism that supports ecological balance, resource efficiency, and community well-being.